Ecodramaturgy Encounters Deleuze and Guattari: A Rhizomatic Reading of Far Away - Gulter, Isil Sahin (Springer, 2025)
This article builds upon ecodramaturgy, which generates lines of flight from anthropocentric perspectives, as its foundation in ecological reciprocity renders it a particularly effective tool in reshaping humanity's attitude to the more-than-human worlds. The article argues that ecodramaturgy offers a visceral way to present and affirm non-hierarchical relationships between humans and nonhumans, paying particular attention to Gilles Deleuze and Felix Guattari's notion of the 'rhizome.' By making use of the relatively new frameworks on ecology and theatre, the article traces the rhizomatic connections in Caryl Churchill's Far Away, thus offering fresh considerations to blur the distinctions between different life forms. The primary argument of the article is that the rhizomatic entanglement between human and nonhuman characters in Far Away provides a non-hierarchical dramatic assemblage in which all life forms are interconnected with each other, embracing multiplicity and heterogeneity. Thus, the article concludes with a discussion of how the rhizomatic reconsideration of the human-nonhuman relationship in a dramatic text can negotiate and reconstruct our material embeddedness in the more-than-human worlds.
Keywords: Deleuze and Guattari; Ecodramaturgy; Rhizome; Assemblage; Anthropocene; Caryl Churchill; Far Away; Humanities; Performance and theatre studies; Ecocriticism